The Small GTPase ROP10 of Medicago truncatula Is Required for Both Tip Growth of Root Hairs and Nod Factor-Induced Root Hair Deformation - Lei, Ming-Juan (Plant Cell, 2015)
Rhizobia preferentially enter legume root hairs via infection threads, after which root hairs undergo tip swelling, branching, and curling. However, the mechanisms underlying such root hair deformation are poorly understood. Here, we showed that a type II small GTPase, ROP10, of Medicago truncatula is localized at the plasma membrane (PM) of root hair tips to regulate root hair tip growth. Overexpression of ROP10 and a constitutively active mutant (ROP10CA) generated depolarized growth of root hairs, whereas a dominant negative mutant (ROP10DN) inhibited root hair elongation. Inoculated with Sinorhizobium meliloti, the depolarized swollen and ballooning root hairs exhibited extensive root hair deformation and aberrant infection symptoms. Upon treatment with rhizobia-secreted nodulation factors (NFs), ROP10 was transiently upregulated in root hairs, and ROP10 fused to green fluorescent protein was ectopically localized at the PM of NF-induced outgrowths and curls around rhizobia. ROP10 interacted with the kinase domain of the NF receptor NFP in a GTP-dependent manner. Moreover, NF-induced expression of the early nodulin gene ENOD11 was enhanced by the overexpression of ROP10 and ROP10CA. These data suggest that NFs spatiotemporally regulate ROP10 localization and activity at the PM of root hair tips and that interactions between ROP10 and NF receptors are required for root hair deformation and continuous curling during rhizobial infection.